1993
DOI: 10.1128/aem.59.12.4203-4210.1993
|View full text |Cite
|
Sign up to set email alerts
|

Ozone inactivation of Cryptosporidium parvum in demand-free phosphate buffer determined by in vitro excystation and animal infectivity

Abstract: Inactivation of Cryptosporidium parvum oocysts by ozone was performed in ozone demand-free 0.05 M phosphate buffer (pH 6.9) in bench-scale batch reactors at 7 and 22°C. Ozone was added to each trial from a concentrated stock solution for contact times ranging from 5 to 15 min. The viability of the control and treated oocysts was determined by using in vitro excystation and infection in neonatal CD-1 mice. It was found that excystation consistently underestimated inactivation when compared with animal infectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…Our findings show that the dye permeability assay indicated a higher survival rate than the in vitro excystation assay did, as previously observed (Jenkins et al 1997), although both methods underestimated the inactivation of C. parvum oocysts in comparison with the animal infectivity methods. These results are in agreement with earlier studies reported for oocysts treated with ozone, UV light or chlorine compounds, which showed neonatal mouse infectivity as the most sensitive indicator of oocyst inactivation (Korich et al 1990;Finch et al 1993;Black et al 1996;Bukhari et al 2000;Quilez et al 2005). At this time, there are no successful protocols for the in vitro excystation of G. muris cysts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings show that the dye permeability assay indicated a higher survival rate than the in vitro excystation assay did, as previously observed (Jenkins et al 1997), although both methods underestimated the inactivation of C. parvum oocysts in comparison with the animal infectivity methods. These results are in agreement with earlier studies reported for oocysts treated with ozone, UV light or chlorine compounds, which showed neonatal mouse infectivity as the most sensitive indicator of oocyst inactivation (Korich et al 1990;Finch et al 1993;Black et al 1996;Bukhari et al 2000;Quilez et al 2005). At this time, there are no successful protocols for the in vitro excystation of G. muris cysts.…”
Section: Discussionsupporting
confidence: 92%
“…In vitro excystation, live-dead vital dyes (DAPI and PI), and infectivity in CD-1 mice were used in this study as indicators of oocyst viability and infectivity. Viability assays by DAPI/PI vital staining have been reported to demonstrate a very good correlation with the maximized in vitro excystation assay - ( Robertson et al 1993;Black et al 1996), although evidence exists to suggest that in vitro excystation assays may overestimate viability in comparison with animal infectivity assays (Finch et al 1993). Our findings show that the dye permeability assay indicated a higher survival rate than the in vitro excystation assay did, as previously observed (Jenkins et al 1997), although both methods underestimated the inactivation of C. parvum oocysts in comparison with the animal infectivity methods.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing these results with those reported in the literature was problematic, as no study has been carried out with the RT-PCR assay as a viability assessment tool. Obtaining a 99.9% inactivation as measured by animal infectivity at room temperature required a CT from 4.6 to 18 depending on the authors (Peeters et al, 1989;Finch et al, 1993;Rennecker et al, 1999). Globally our data are in agreement with published ozone inactivation studies.…”
Section: Discussionmentioning
confidence: 99%
“…The transmissive oocyst is resistant to the levels of chlorine routinely used in water treatment plants (West, 1991) and sand-bed filtration is currently the only effective method of removal (Smith, 1992). Ozonation is currently being investigated as an alternative (Finch et al, 1993a) although the high concentrations required for effective removal may be impossible to achieve at the normal temperatures used in waste water treatment plants (Robertson et al, 1994). The detection of cryptosporidia in both water and faecal samples relies on microscopic identification of oocysts (Smith et al, 1993).…”
Section: Cryptosporidiummentioning
confidence: 99%